2021
DOI: 10.1080/17453674.2021.1881241
|View full text |Cite
|
Sign up to set email alerts
|

Severely injured patients do not disappear in a pandemic: Incidence and characteristics of severe injuries during COVID-19 lockdown in Finland

Abstract: Background and purpose — COVID-19 lockdowns have resulted in noteworthy changes in trauma admissions. We report and compare the incidence and characteristics of severe injuries (New Injury Severity Score [NISS] > 15) during the COVID-19 lockdown in Finland with earlier years. Methods — We retrospectively analyzed incidence rate, injury severity scores, injury patterns, and mechanisms of injury of all severely injured patients (NISS >15) in 4 Finnish hospitals (Tampere University Hospital, Kuopio Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 9 publications
6
48
1
4
Order By: Relevance
“…Systolic blood pressure and respiratory rate were signi cantly worse during the Pandemic in our study, although ISS and GCS were unchanged. Other authors reported signi cant changes both in the anatomical and physiological markers of severity between the two periods [13,14,32]. Our current study has shown that low GCS, higher ISS, and admission to ICU are the most signi cant clinical predictors of mortality among patients who died, similar to our reported previous studies before the pandemics [33][34][35].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Systolic blood pressure and respiratory rate were signi cantly worse during the Pandemic in our study, although ISS and GCS were unchanged. Other authors reported signi cant changes both in the anatomical and physiological markers of severity between the two periods [13,14,32]. Our current study has shown that low GCS, higher ISS, and admission to ICU are the most signi cant clinical predictors of mortality among patients who died, similar to our reported previous studies before the pandemics [33][34][35].…”
Section: Resultssupporting
confidence: 89%
“…periods [13,14,32]. Our current study has shown that low GCS, higher ISS, and admission to ICU are the most signi cant clinical predictors of mortality among patients who died, similar to our reported previous studies before the pandemics [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[8][9][10][11][12][13] A previous Finnish study showed that the rate of severely injured patients remained stable during the pandemic. 14 Parallel results were reported when the pandemic also increased referrals to major trauma centers in the pediatric population. 9 A previous study from Finland reported a decrease in incidence of pediatric trauma operations during the lockdown, mostly due to a decreased rate of lower limb trauma operations.…”
Section: What Are the New Findings?mentioning
confidence: 64%
“…Non-natural deaths were selected as a comparison group for two reasons. First, while it has been documented that overall emergency department visits have decreased, trauma-related visits for severe injury were less impacted ( Riuttanen et al, 2021 ). Additionally, a study examining the trend of trauma emergency department visits before and during the pandemic found that patients who were treated during the pandemic had higher injury severity scores when compared to patients treated prior to the pandemic ( Ghafil et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%